RELEVANSI KARYA PENELITIAN MIGRASI DALAM PEMBANGUNAN - Suko Bandiyono (Jurnal Kependudukan Indonesia, 2008)
Migration issue has been neglected during the last decade, although it has a significant relation with development issue. Migration, as a part of demographic component, has changed demographic structure and the society life. This article reviews the existing migration-related publications, describes migration experiences of the society and highlights their relations with development. This article suggests that migration should be taken into account as an independent variable when examining population phenomena.Keyword: Migration studies, National development